Construction of brick wall on bungalow / Muhamad Badrul Hisham Mohamad Khairi - Mohamad Khairi, Muhamad Badrul Hisham (Universiti Teknologi MARA, Perak, 2022)
This internship report contains five chapters altogether mainly about the works related to the course that have been attended during the internship period from 06th September 2021 until 07th January 2022 at Raz Intan Development Sdn Bhd. It is cannot be denied that there are lots of new knowledge from the internship.Chapter 1 is basically introduction about internship, company and report title. Introduction of internship is the overview of the internship programed itself such as objective and the purpose of internship. The introduction of company is about the company biography and history. In four months internship, students are compulsory to choose a title or scope of work to be reported and submit to university. Therefore, this report is about maintenance and repairing work of housing before handover process. After that, chapter 2 will be described about case study of project named of the work. This part will be present detail information of the brickwork.Followed by Chapter 3 that been discussing about construction of brickwork since the title main report is construction of brick wall on bungalow. There is a literature review about brick and tools needed in that work. There are also common problems happened to the brickwall and the common remedies that are function while last longer. contains the process of the repairing work from beginning until end of the work. It is the work that has been monitored from the first day of work. The materials and the tools used by company also will be described in detail. The final chapter will be chapter 4 where the recommendation and conclusion can be gathered from observation and site monitoring that have been done.